Pendidikan Intrepreneurship Berbasis Multikultural di Pondok Pesantren Fathul Ulum Gerdu Laut Jombang - Burhanudin (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2022)
This paper raises the theme and describes Entrepreneurship built in Islamic boarding schools to realize the character of students which is expressed through tolerant, creative and innovative attitudes and behaviors to carry out an activity. This paper also analyzes the spirit of multiculturalism that is built on the students of the Fathul Ulum Gerdu Laut Jombang Islamic Boarding School in carrying out entrepreneurial activities at the boarding house. The formulation of the problem in this article includes: a) Empowering the entrepreneurial awareness of students at the Fathul Ulum Islamic Boarding School Jombang, b) Instilling multiculturalism values ​​in students at the Fathul Ulum Islamic Boarding School Jombang. This research uses qualitative research or field research. For data collection procedures through interviews, observation and documentation by checking the validity of the data through the participation of researchers, persistence, triangulation of data and sources. Keywords: Entrepreneurship, Multiculturalism